Implementation of Triangle Learning Based on Acehnese Batik Culture at MTs Keutapang Dua - Fahradina, Nova; Rahmatina, Siti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Mathematics is one of the subjects taught at various levels of school because this science has a close relationship and an important role in everyday life. Triangles are one of the important materials taught in schools. However, many students still experience difficulties in mastering this material. One way to overcome this problem is through Ethnomathematics-based learning. Ethnomathematics is a mathematics learning approach that integrates cultural elements and local wisdom of a region. This study aims to determine how the implementation of triangle material learning based on Acehnese batik culture at MTS Keutapang Dua. The method used is quantitative research with a quasi-experimental type. The research design applied is a posttest-only control design. The experimental class received learning about triangles integrated with Acehnese batik motifs, while the control class received conventional learning. The results of the study indicate that the implementation of Acehnese batik culture-based learning has a positive impact on student learning outcomes.